Le glanage alimentaire en milieu urbain, ou la constitution de « protections rapprochées » - Martin Manoury (Tracés, 2021)
Food gleaning is usually considered as a subsistence practice, related to scarcity and hunger. This paper revisits this assumption by focusing on gleaning by the lower fractions of the working classes. Based on data from fieldwork still in progress, this article shows that even though gleaning is a way of consuming food that is excluded from the official market supply channels, it cannot be reduced to that. First, through an interactional approach, we explain how this practice can, in some cases, make visible the constitution of close protection, based on moral values of reciprocity and solidarity. Secondly, this article takes a dispositional approach, by analysing the genesis of the non-market economic arrangements of one of the gleaners. We show that these arrangements are not only determined by situations of survival struggles, lack and hunger, but that they are established during past stages of school and professional socialisation, transforming both the modalities of action and the meaning given to the practice.